Patient characteristics, Bacteriological profile & outcome of Neonatal Sepsis: A Hospital Based Study - Jahan, Nasim; Haque, Zabrul SM; Mannan, Md Abdul; Akhter, Morsheda; Yasmin, Sabina; Akhter, Shirin; Talukder, Abu Mohammad; Dey, Sonjoy Kumar (Community Based Medical Journal, 2013)
Neonatal sepsis is a major cause of mortality and morbidity in newborn. The spectrum of bacteria which causes neonatal sepsis varies in different parts of the world. The organisms responsible for early onset and late onset sepsis are different. The objective of the study was undertaken to determine the pattern of bacterial isolates responsible for early and late onset neonatal sepsis. A prospective descriptive study over the period of one year was conducted at the Department of Neonatal Intensive care unit of Ad-din Womens Medical College and Hospital, Dhaka, Bangladesh.Organisms were isolated from 8.7% of collected blood samples. The male female ratio of culture proven sepsis was 1.7:1. More than half (52.8%) of the evaluated neonates were preterm. & 56.3% had low birth weight. The gram positive and gram negative bacteria accounted for 24.1% and 75.9% of the isolates respectively. Around three fourth of the neonates (75.8%) presented with early onset sepsis, while 24.2% presented with late onset sepsis. Acinetobacter was the most common pathogen both in early onset (70%) and late onset (30%) sepsis. Pseudomonas (89.4%) was the second most common pathogen in early onset sepsis. Total mortality rate was 5.7%. Pre term, low birth weight and gram negative sepsis contributes majority of mortality.Gram negative organism especially Acinetobacter found to be commonest cause of sepsis. Pseudomonas was second most common but contributed highest in late onset sepsis and neonatal death due to sepsis. DOI: http://dx.doi.org/10.3329/cbmj.v2i1.14184 Community Based Medical Journal Vol.2(1) 2013 49-54